Systematic Literature Review: Pengaruh Indeks Pembangunan Manusia (IPM) Terhadap Pertumbuhan Ekonomi - Antje Tuasela (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
One way to measure the success or performance of a country or region in the field of human development is to use the Human Development Index (IPH). The purpose of this study is to examine the effect of the human development index (HDI) on economic growth. The method used in this article is a qualitative method with a literature study or Library Research. The aim is to analyze the comparison of existing theories with previous theories in the research literature. The literature used is literature from the results of research or studies presented in scientific articles. All articles used are sourced from electronic data literacy search engines Mendeley and Google Scholar. The literature used is in accordance with the qualitative approach with the type of literature research. Based on a review of literature review of several articles in national and international journals in this article, it can be concluded that the development of the human index (HDI) does not have a significant effect on economic growth. Keywords: Systematic Literature Review, Human Development Index (HDI), Economic Growth